A case study of percutaneous epidural stimulation to enable motor control in two men after spinal cord injury - Ashraf S. Gorgey; Robert Trainer; Tommy W. Sutor; Jacob A. Goldsmith; Ahmed Alazzam; Lance L. Goetz; Denise Lester; Timothy D. Lavis (Nature Communications, 2023)
Abstract Two persons with chronic motor complete spinal cord injury (SCI) were implanted with percutaneous spinal cord epidural stimulation (SCES) leads to enable motor control below the injury level (NCT04782947). Through a period of temporary followed by permanent SCES implantation, spinal mapping was conducted primarily to optimize configurations enabling volitional control of movement and training of standing and stepping as a secondary outcome. In both participants, SCES enabled voluntary increased muscle activation and movement below the injury and decreased assistance during exoskeleton-assisted walking. After permanent implantation, both participants voluntarily modulated induced torques but not always in the intended directions. In one participant, percutaneous SCES enabled motor control below the injury one-day following temporary implantation as confirmed by electromyography. The same participant achieved independent standing with minimal upper extremity self-balance assistance, independent stepping in parallel bars and overground ambulation with a walker. SCES via percutaneous leads holds promise for enhancing rehabilitation and enabling motor functions for people with SCI.